PENGARUH VARIASI POLYVINYL ALCOHOL (PVA) TERHADAP KARAKTERISTIK MEMBRAN KITOSAN TERMODIFIKASI SEBAGAI SLOW-RELEASE FERTILIZER (SRF) PUPUK NPK - dinda putri aliyanti; Sari Edi Cahyaningrum (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2026)
The use of conventional NPK fertilizers in the agricultural sector results in relatively low nutrient utilization efficiency due to losses through volatilization, nitrification, and leaching. One effort to address this issue is the development of NPK fertilizers with controlled nutrient release, or slow-release fertilizers. This study aims to determine the effect of varying Polyvinyl Alcohol (PVA) content on the characteristics of SRF membranes. The membranes were synthesized using the solvent casting method, in which the membrane solution was poured into petri dishes and the solvent was evaporated to produce dry SRF membranes. The results showed that as the PVA content added to the SRF matrix increased, the mass ranged from 0.0573 to 0.0602 grams. The degree of swelling produced by the four variations ranged from 106.19% to 134.09%. The resulting porosity ranged from 0.20% to 0.40%. This indicates that the addition of PVA affects the physical characteristics of the membrane.